Moringa Growth Response in Treatment of Bokashi Composition and Dosage of Moringa Leaf (Moringa oleifera) Using Subsoil - Nurlianti Nurlianti; Nurseha Nurseha; Ovian Ade Putra; Prihanani Prihanani; Farida Ariyani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Subsoil soil which is at a depth of more than 30 cm below the topsoil is a marginal soil for agricultural cultivation but has great potential for utilization. Improvement of subsoil soil with the use of organic fertilizers alone has been widely carried out. However, the use of moringa leaf bokashi fertilizer is thought to be able to improve the subsoil physically and chemically. The aim of the research was to find out the composition of the best moringa leaf bokashi fertilizer and the right dosage for the growth of moringa. Research using Completely Randomized Design. The first factor was the composition of moringa leaf bokashi, biochar and cow manure (K), namely K1 ratio of moringa leaves: biochar: cow manure (1:1:1); K2: (2:1:1); K3 (3:1:1). The second factor is the dose of moringa leaf bokashi fertilizer. Bo: control 5; B1:10; B2: 20; B3: 30; B4: 40 tons per hectare. The results showed that the K1 composition showed the highest plant height, number of primary roots, and canopy wet weight. A dose of 10 tons per hectare (B1) showed the best growth of Moringa seedlings with the highest dry weight of canopy. Keywords:  Bokashi, Composition, Dosage, Moringa leaves, Moringa seedling